(untitled) (Indonesian Journal of Agrarian Law, 2026)
Coal mining in Muara Enim Regency makes a significant contribution to the national and regional economies; however, it also causes serious environmental, social, and health impacts on the surrounding communities. Although national legal frameworks such as Law No. 32 of 2009 on the Environment and the Mineral and Coal Law have established principles of environmental protection and community rights, their implementation on the ground still faces many challenges. This study aims to analyze the effectiveness of legal protection for communities affected by coal mining in Muara Enim, using a qualitative approach and Philipus M. Hadjon’s theoretical framework of legal protection, which encompasses preventive and repressive dimensions. The research findings indicate that although legal mechanisms such as Environmental Impact Assessments (EIA), land reclamation, and compensation are available in theory, their implementation is often hindered by weak oversight, lack of transparency in information, and limited legal capacity among communities. Furthermore, the reclamation process has not fully succeeded in restoring the ecological functions of the land, while community access to justice remains constrained by bureaucracy and power imbalances. This study recommends strengthening oversight institutions, increasing community participation, ensuring transparency in permitting data, and reforming the compensation system to achieve substantive environmental justice.